Functional Outcomes after Transanal Surgery - Foppa, Caterina; Carrano, Francesco Maria; Spinelli, Antonino (Clinics in Colon and Rectal Surgery, 2022)
Transanal surgery has gained in popularity during the latter part of the last decade for both rectal cancer and benign disease. The current role for local excision of early rectal neoplastic lesions has expanded due to better understanding of risk factors for lymph node metastasis and heightened awareness for the long-term sequelae of radical surgery. Transanal resection of the rectum (both for cancer or inflammatory bowel diseases) has now been established as a successful procedure that overcomes some of the limitations of the abdominal approaches. Once the feasibility, safety, and the oncologic results of transanal minimally invasive approaches for patients with rectal cancer have been acknowledged, quality of life and functional outcomes have become increasingly important issues. This article provides an overview of the different techniques currently available for the minimally invasive transanal treatment of rectal lesions, particularly focusing on functional outcomes.
Keywords: rectal cancer; transanal endoscopic surgery; minimally invasive surgery; TaTME